2015
DOI: 10.1021/jacs.5b10194
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biosynthesis of the Core Scaffold of the Thiopeptide Thiomuracin

Abstract: Thiopeptides are potent antibiotics that inhibit protein synthesis. They are made by a remarkable post-translational modification process that transforms a linear peptide into a polycyclic structure. We present here the in vitro biosynthesis of the core scaffold of thiomuracin catalyzed by six proteins. We show that cyclodehydration precedes dehydration, and that dehydration is catalyzed by two proteins in a tRNAGlu-dependent manner. The enzyme that generates the pyridine core from two dehydroalanines ejects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
279
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(284 citation statements)
references
References 27 publications
5
279
0
Order By: Relevance
“…S5). A similar pattern of multiple glutamylations has previously been observed for nonthiopeptide RiPP pathways (22,25); however, in the in vitro reconstituted thiomuracin system, only a monoglutamylated intermediate accumulates when the TclL ortholog (TbtC) is omitted (11). This discrepancy may be due to the different reaction conditions (in vitro versus in vivo) or to an intrinsic difference in how this two-step dehydration process is coordinated in the two biosynthetic systems.…”
Section: Tclp Mediates the Transition Between Two Phases Of Core-peptidesupporting
confidence: 66%
See 2 more Smart Citations
“…S5). A similar pattern of multiple glutamylations has previously been observed for nonthiopeptide RiPP pathways (22,25); however, in the in vitro reconstituted thiomuracin system, only a monoglutamylated intermediate accumulates when the TclL ortholog (TbtC) is omitted (11). This discrepancy may be due to the different reaction conditions (in vitro versus in vivo) or to an intrinsic difference in how this two-step dehydration process is coordinated in the two biosynthetic systems.…”
Section: Tclp Mediates the Transition Between Two Phases Of Core-peptidesupporting
confidence: 66%
“…Previous studies showed only MP1 is produced from the full set of genes, whereas only MP2 is formed in the ΔTclS strain (13). the recent in vitro thiomuracin study (11), may initiate processing. Indeed, the TclE peptide remains unmodified in the TclJ-defective strain (Fig.…”
Section: Tclp Mediates the Transition Between Two Phases Of Core-peptidementioning
confidence: 95%
See 1 more Smart Citation
“…For a typical thiopeptide gene cluster in nature, one often encounters numerous additional genes that obscure the simplicity of central thiopeptide chemistry. The recent in vitro reconstitution of the thiomuracin biosynthetic pathway illustrates this simplicity (17). In that study, five different protein enzymes, along with an additional RiPP precursor peptide recognition element (RRE)-containing protein, were found to be sufficient for the synthesis of a bioactive thiopeptide scaffold.…”
mentioning
confidence: 99%
“…In 2009, multiple independent researchers reported this general scheme for thiopeptide synthesis (11)(12)(13)(14)(15). In the years since, several additional biosynthetic principles have been elucidated (16)(17)(18). The process appears to involve three core steps: (i) cyclodehydration/oxidation of Cys residues to form thiazole heterocycles (Ser and Thr residues may also be modified to oxazoline or oxazole), (ii) dehydration of Ser and Thr residues yielding dehydroalanines and dehydrobutyrines, respectively, and (iii) cycloaddition of two of the dehydrated residues to yield the final macrocyclic thiopeptide scaffold (Fig.…”
mentioning
confidence: 99%